Relationship between humeral head translation, spur formations, and the locations of tendon tears in massive rotator cuff tears - Yuki Yoshida; Atsushi Yoshida (BMC Research Notes)
Abstract Objective This study aimed to clarify the relationship between the directions of humeral head translation, the presence of acromial or coracoid spurs, and the locations of tendon tears in massive rotator cuff tears. Thirty shoulders from thirty patients with massive rotator cuff tears who underwent reverse shoulder arthroplasty were included. Preoperative 3DCT classified humeral head translation into three groups: minimal type, posterosuperior type, and anterosuperior type. The presence of acromial or coracoid spurs was also assessed. Preoperative MRI and intraoperative findings determined the torn tendons in each rotator cuff, along with ruptures of the anterior fascia covering the subscapularis or the long head of the biceps tendon (LHB). Relationships between humeral head translations, spur formations, and tendon tear locations were analyzed using chi-square tests and adjusted standardized residuals. Results Acromial spurs were more frequent in the posterosuperior type, while coracoid spurs, subscapularis tears, anterior fascia ruptures, and LHB ruptures were significantly associated with the anterosuperior type. Anterior fascia ruptures were significantly less frequent in the minimal type. Anterosuperior humeral head translation and coracoid spurs indicate subscapularis tears, anterior fascia ruptures, and LHB ruptures.